Europa i chrześcijaństwo: historia i przyszłość - Begzos, Marios (Elpis, 2014)
Is Europe Christian or not? This was the question that dominated some time ago the intense discussion duringthe working-out of the European Constitution. Two were the contrasting standpoints, one affirmative and one negative, which in turn set off a lot of contending. The final outcome was a suppression of the whole issue as far asthe constitutional document is concerned, and an indirect reference to the humanistic legacy of Europe; a reference incorporated within the preamble of the ultimate constitutional chart of the European Union – which, of course, isstill in the voting process.